Sex hormones, exercise and women : scientific and clinical aspects / Anthony C. Hackney, editor. - Hackney, Anthony C. (Springer, 2023)
This work compiles and synthesizes the latest research and clinical evidence regarding the intricate relationship between sex hormones and the physical activity level and overall health of the female endocrine system across the lifespan. Expert authors from around the world discuss in detail the impact of sex hormones on energy metabolism, cardiorespiratory system, nervous system, and musculoskeletal health, as well as environmental and psychological factors affecting exercise and sexual health. Considerations of the hormonal and physiological changes to the menstrual cycle and in menopause due to exercise receive chapters of their own.